The Treasure Chest - HUNT, RODERICK (China Oxford, 2012)
"Social Problems" by John J. Macionis provides an in-depth analysis of the major social issues that affect contemporary society, examining their causes, consequences, and potential solutions through a sociological lens
A Levels